Measuring the Climate and Environmental Impacts of Sustainable Tourism Development: The Case of Latvia - Grizane Tamara; Blumberga Dagnija (Environmental and Climate Technologies)
Climate and environmental change is a growing theme in the post-Covid-19 era of continued tourism growth. Tourism is a serious polluter of the environment and a rapid response to climate change is needed. Latvia, like the EU, is looking for ways to balance the economic, social and environmental impacts of the SDGs of the 2030 Agenda, which is not possible without scientific research. The selection of methods for assessing the climate and environmental impacts of sustainable tourism development is the basis for this. The study adopts a mixed methods approach, combining qualitative methods (content analysis, review of existing research) with quantitative methods. A multi-criteria decision-making method, the Analytic Hierarchy Process (AHP) with empirical analysis of the resulting weights, was used to select the evaluation methods. The bibliographic and citation database Scopus, a multidisciplinary database of scientific publications, was used to find the most popular methods for assessing the climate and environmental impacts of sustainable tourism development (ISTD), and to select and identify methods for assessing the climate and environmental impacts of tourism development in the interests of tourists, local residents, regions and the country. In real circumstances, the choice of method should be based on geographical typology, territorial dimension and sufficient indicators of tourism sustainability. The authors recommend that the choice of methods for assessing the climate and environmental impacts of sustainable tourism development should be tested with a larger number of experts and that the Sustainable Tourism Development Indicators methodology (SusTour-Index) should be used.